The Prevalence and types of congenital anomalies in new born - Ghalie, Mazin; Jouni, Oudai; Hatem, Lobna (Latakia University Journal -Medical Sciences Series, 2020)
Objective: The primary objective; determin the prevalence and types of congenital anomalies among newborns admitted in Tishreen Hospital. The secondary objective : determin the relationship between the congenital anomalies and ,sex of the baby, age of mother, consanguinity of parents, family story. Methods: The study sample included neonates with congenital malformations who were admitted to the Tishreen Hospital during 2018- 2019. The following is done for each child who has seen congenital malformation : Echocardiography ,echoencephalogram ,abdominal ultrasound, and another investigation according to examination assets .. Results : Congenital abnormalities were observed in 60 out of 1871 child, giving a prevalence of 3,2%.Among the various types of congenital abnormalities , the highest percentage was observed in the ones related to digestive system malformations(43,3), followed by nervous and heart anomalies (21,6%), the gender of fetus affected the prevalence of congenital abnormalities , males comprised 65% of anomalies ,females comprised 33,3% births . the highest congenital abnormality is observed among babies delivered by mother age between (30-45)years . from 60 cases with anomalies ,35(58,3%) cases were from familial marriage هدف الدراسة: -الهدف اساسي : - تحديد نسبة انتشار التشوهات الخلقية الملاحظة لدى حديثي الولادة المقبولين في شعبة أمراض الوليد في مشفى تشرين الجامعي . دراسة نوع التشوهات الخلقية الملاحظة لدى حديثي الولادة المقبولين في شعبة أمراض الوليد. - الهدف الثانوي: - دراسة علاقة هذه التشوهات مع كل من: جنس الوليد، ترتيب الحمل ، عمر الأم ، وجود قرابة بين الوالدين ، وجود قصة عائلية . طريقة البحث والمرضى: شملت الدراسة سجلات الولدان المصابين بتشوهات خلقية ، الذين تم قبولهم في شعبة الوليد والخديج في مشفى تشرين الجامعي في اللاذقية بين عامي 2018-2019 . _ أجري إيكو قلب ، إيكو بطن ، إيكو عبر اليافوخ الأمامي لدى كل تشوه خلقي، كما أجريت استقصاءات أخرى حسب المعطيات السريرية والتوجه السببي . النتائج: تم قبول 1871 وليداً في شعبة أمراض الخديج والوليد في مشفى تشرين الجامعي في اللاذقية خلال فترة الدراسة الممتدة بين عامي 2018-2019, إذ بلغ عدد الولدان المصابين بالتشوهات الخلقية 60 وليداً (39ذكراً، 21أنثى ) مما شكل نسبة انتشار3،2% ، و توصلت هذه الدراسة إلى أن نسبة تشوهات الجهاز الهضمي هي الأعلى إذ بلغت ( 43،3% ) ، تلتها تشوهات الجهاز العصبي وتشوهات الجهاز القلبي الوعائي ، إذ بلغتا(6،21% ) ، وبالنظر إلى جنس الوليد فإن( 39) من الذكور سجلت لديهم تشوهات خلقية أي بنسية(65%)، مقابل بينما عانت21 من الإناث منها ،أي بنسبة (35%) ، وتوصلت هذه الدراسة إلى أن نسبة التشوهات الخلقية تزداد عندما تنتمي الأمهات إلى المجموعة العمرية(30-45) سنة .كما سجلت 35 حالة تشوه خلقي من عائلاتٍ بدرجات قرابة مختلفة أي بنسبة 58,3%.